Sportorthopädie - Beitzel K; Reuter S; Imhoff AB; Braun S (Deutsche Zeitschrift für Sportmedizin)
Overhead and throwing sports can result in structural longterm damage to the athletes shoulder due to their specific movement pattern. An effective throwing technique necessarily requires extreme abduction and external rotation of the shoulder joint, which results in a permanent overload of capsular and muscular structures. The changes associated may also lead to structural damagesor shortterm consequences in terms of acute injury. The pathology is complex and requires a differentiated diagnosis and therapy. Several theories exist for the development of pathology of a throwers shoulder. The known theoretical models can be generally combined to basic principles. Shortening of the dorsal capsular structures results in a decreased internal rotation in high abduction and appears already in the early stages as a glenohumeral internal rotation deficit (GIRD). Repetitive distention of the anterior capsule withsimultaneous shortening of the dorsal capsular structures lead to a decentralization and superior translation of the humeral head. This results in internalimpingement in the area of the posteriorsuperior glenoid (PSI) and detachment of the biceps tendon anchor (SLAP). Unequal distribution of training loads lead to a weakening of the external rotating muscles of the rotator cuff. The presented 5 point check is based on the usual explanatory models for pathology of athletes shoulders. In clinical practice, this approach allows a practical evaluation of this complex pathology. The focus is on addressing the identified functional deficits. If there are any structural damages to the rotator cuff, the labrum, the biceps tendon or conservatively not treatable movement restrictions, a surgical procedure is indicated in rare cases.KEY WORDS: Athletes Shoulder, Throwers Shoulder, Posterior Superior Inpingement, PSI, GIRD